(untitled) (Revista de Biología Marina y Oceanografía, 2022)
Pandarus boscii was previously reported in Mustelus mustelus (basionym: Squalus mustelus), but the original description of P. boscii was incomplete and inadequate. P. boscii is currently accepted as a synonym of Pandarus bicolor. Females of P. boscii differ in that the body is colorless or pale (in P. bicolor the cephalothorax is brown and the dorsum is yellow), the first and distal segments of the antennule have 23-25 plumose setae and 12 setae, respectively (in P. bicolor are 24-26 plumose setae and 13 setae), mandibular blade with 7-8 teeth (in P. bicolor are 8 teeth), maxilliped with one seta (in P. bicolor absent), proximal exopodal segment of the second leg with 5 spines (in P. bicolor are 6 spines). Significant differences were observed between male individuals of the two species, such as: smaller total body measuring 3.5 mm in length (in P. bicolor 3.9 mm), first and distal segments of the antennule with 15-17 plumose setae and 14 setae, respectively (in P. bicolor 26-27 plumose setae and 12 setae), mandibular blade with 7 teeth (in P. bicolor are 8), first antennal segment with one process and maxilliped with one seta (in P. bicolor absent), leg 5 with one naked and one plumose seta (in P. bicolor 3 plumose setae and a robust seta), distal exopodal segment of 3 and 4 legs with 2 spines (in P. bicolor 4 spines), distal endopodal segment of 3 and 4 legs with 4 and 3 setae, respectively (in P. bicolor with 5 and 4 setae). A detailed description of P. boscii is provided from individuals found on the body surface and fins of the spiny dogfish Squalus acanthias, recently collected in the Sea of Marmara, Turkey. Therefore, according to the results Pandarus boscii and P. bicolor are different species.